Factors influencing micronutrient bioavailability in biofortified crops. Issue 1 (23rd December 2016) - Bechoff, Aurélie; Dhuique‐Mayer, Claudie
Abstract : Dietary and human factors have been found to be the major factors influencing the bioavailability of micronutrients, such as provitamin A carotenoid (pVAC), iron, and zinc, in biofortified crops. Dietary factors are related to food matrix structure and composition. Processing can improve pVAC bioavailability by disrupting the food matrix but can also result in carotenoid losses. By degrading antinutrients, such as phytate, processing can also enhance mineral bioavailability. In in vivo interventions, biofortified crops have been shown to be overall efficacious in reducing micronutrient deficiency, with bioconversion factors varying between 2.3:1 and 10.4:1 for trans ‐β‐carotene and amounts of iron and zinc absorbed varying between 0.7 and 1.1 mg/day and 1.1 and 2.1 mg/day, respectively. Micronutrient bioavailability was dependent on the crop type and the presence of fat for pVACs and on antinutrients for minerals. In addition to dietary factors, human factors, such as inflammation and disease, can affect micronutrient status. Understanding the interactions between micronutrients is also essential, for example, the synergic effect of iron and pVACs or the competitive effect of iron and zinc. Future efficacy trials should consider human status and genetic polymorphisms linked to interindividual variations.